Impact of firm-level characteristics and international marketing strategies on export performance of SMES in South Africa - Siddiqui, Ammar (My University, 2021)
Internationalization has caused numerous businesses across the world to extend their operations to foreign countries. Amongst the various forms of internationalization, such as direct investment, franchising and joint ventures, the primary and most common mode used by Small and Medium Enterprises (SMEs) is exporting. Exporting allows businesses to function in their home country and serve customers in other countries. Exporting relieves businesses from domestic competition, increases production, from which economies of scale, competitive prices and competitive advantages are gained. Despite these advantages, there are reports that limited SMEs in emerging economies like South Africa that are facing increasing competition from international forms entering their markets are exporting. Such reports raise questions as to the factor that becomes barriers for SMEs in South Africa to export. Previous studies have produced mixed findings, with some suggesting that exporting determinants are SMEs characteristics in terms of size and age, others suggesting managerial capabilities and characteristics and some contending that it is environmental factors and competence in dealing with expert market conditions and requirements. Considering the mixed findings from literature, there was a need for a consolidated study to identify country-specific factors that will propel SMEs in South Africa to not only export to perform optimally and superiorly. Even though the resource-based view (RBV) and dynamic capabilities view (DCV) theorists posit that firm performance is guaranteed when firms possess resources (tangible and intangible) and dynamic capabilities to adapt marketing strategies to changing market conditions, researchers have ignored the mediating role of the resultant marketing strategies in the relationships between performance drivers and export performance. Thus, this research had two main objectives: 1) examine the extent to which firm characteristics (firm size, age of the firm and employee education), managerial characteristics (international experience, education level, foreign language knowledge, risk taking ability, rigidness, proactive approach), environmental characteristics (psychic distance, cultural specificity), export market competencies (commitment, international expertise, market knowledge, innovation) impact both optimal and superior export performances); 2) test the mediating role of international marketing strategies in the relationships between the sets of drivers and export performance (subjectively) of South African SMEs. An integrated conceptual framework was developed delineating these relationships. iii To empirically test the conceptual framework, data was collected from 350 respondents of SMEs involved in export activities, located in the Gauteng and Western Cape of South Africa. Convenience sampling method was used in the research. The findings indicate that optimal export performance was significantly driven by an organization’s characteristics (i.e., size and education of employees), environmental characteristics of the firm (only psychic distance) and export market competence (internal market knowledge and experience, innovation and commitment. Superior export performance was significantly impacted by managerial characteristics (i.e., Foreign Language Expertise, International Experience, and Education level), Personality Factors (i.e., Risk Taking Ability, Rigidness, and Proactive Approach). The international marketing strategies and managerial characteristics had the greatest influence on the optimal export performance of the organisation, while the market competencies made the greatest impact on optimal export performance. The developed integrated model explained 87.6% of superior export performance, 78.5% of optimal export performance and 79.2% of international marketing strategy. With this high explanatory powers, this research theoretical contributes in the field of international marketing and strategic management by providing a holistic model with which to identify various factors and their facets helping and hindering SMEs to perform superiorly and optimally in not only an emerging market context but also in an African context. This study also theoretically contributes by confirming the RBV and DCV theories in an African market context. Practically, and for the SMEs that perform well, they can use insights from this study to identify what they are doing rightly. For the SMEs that perform poorly or are planning to export, this comprehensive findings will be a rich guide into internal factors (managerial and firm characteristics and export market competence) and environmental factors to focus on for effective strategy implementation and resultant superior and optimal export performances. Future research should test this model with a larger sample size and in other emerging and developing countries.
A thesis submitted to the in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, School of Business Science, University of the Witwatersrand, Johannesburg, 2021
Keywords: Strategies; SMEs; South Africa; Performance; UCTD; SDG-8: Decent work and economic growth